AB1085 The factors affecting remission in jia patients, single centre results. (12th June 2018) - Sozeri, B.; Demircan Bilen, T.; Kurtulus, D.; Islek, I.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in childhood. Nowadays, in the management of JIA, clinical remission is the accepted goal. However, remission is much associated with the JIA subtype and inversely with suggested predictors for poor outcome. Objectives: The aim of the study is to evaluate the predictors of clinical outcome in patients with juvenile idiopathic arthritis Methods: This was a single-centre, an observational study including children diagnosed with JIA at Health Sciences University Istanbul, Umraniye Education and Research Hospital, Turkey, between June 2016 and January 2018. All patients were evaluated at the time of diagnosis, and at 3 months of their disease. We routinely collected the patients' baseline profile which included the age of disease onset, gender, number of active joints, patients'and physicians'global assessment of disease activity (PGA, range from 0 to 10 mm; 0 is the best score), the JADAS 27 score. and therapy. Patients were identified through the divisional database which includes all patients seen in the rheumatology clinic. Results: A total of 141 JIA patients were included in the analysis. The mean follow-up duration of these patients was 23.36 months (range from 12 to 156 months). We examined 71 joints in all patients. At the time of diagnosis, it was seen that they were frequently in knee joint (61.7%) and sacroiliac joints (34.8%). The rate of improvement of joints in the last visit was found to be metatarsophalangeal joints (100%), sacroiliac joints (79%) and knee joints (44.8%), respectively. The non-systemic group (n=133) was evaluated for initial steroid use, among the patients, 54 (% 41) had steroid therapy at the time of diagnosis. There was seen that 29 of the 141 patients (20.6%) were in the remission in 3 months of follow-up. According to subtype of JIA patients, systemic patients (62.5%) were frequently in remission at 3 months. At the end of the study, of the 141 patients, 72 (51.1%) achieved remission and were assigned to the remission group. Among the patients in the remission group, 44 (49.4%) had episodes of disease flares. The other 30 (40.5%) patients did not have disease flares. Comparing the baseline data in the remission group and non-remission group, there was no difference between these two groups in disease onset age, gender, JIA subtypes, number of active joints at disease onset and JADAS 27 scores and used steroid therapy. We also analysed whether each group used biological drugs and analysed the duration of starting biologic therapy. Among 72 patients achieved remission, 17 (23.6%) patients had at least one biological drug. There was no difference between two groups. The median time of biologic drug starting was 12 (interquartile range (IQR), 12) months. There was longer time of biologic drug starting in non-remission group than remission group (32.3±36.2 vs 25.0±31.4, p>0, 05). We determine that in systemic and poli JIA patients who were used biological therapy were found to have a high percentage of achieved to remission Conclusions: JIA is a heterogeneous disease with significant variability in course and long-term outcome. No parameter could be used as a single predictor of long-term outcomes. Standardised baseline work-up, disease activity evaluation and a definition of a treat to target approach will result in better health outcomes for JIA patients Disclosure of Interest: None declared